The real determinants of power generation and maintenance during extreme strength endurance efforts: the 3-Minute Burpee Test - Borysławski, Krzysztof; Podstawski, Robert; Ihász, Ferenc; Żurek, Piotr (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. Anthropometric characteristics and physical activity(PA) levels are often considered as potential variables that can besignificantly correlated with specific motor abilities. Aim of Study.The aim of this study was to evaluate the relationships betweenanthropometric characteristics and motor abilities with the use ofa methodological approach that is rarely applied in physical culturesciences. The correlations between body mass, body height, BMIand PA levels vs sequential power decrease in successive minutesof the 3-Minute Burpee Test (3-MBT) were analyzed. Materialand Methods. The study involved 359 full-time university studentsaged 19-22, including 163 male (20.4 ± 0.67 years) and 196 female(20.4 ± 0.65 years) participants. Anthropometric characteristics(body mass, height and BMI), PA level (MET units) weremeasured according to standardized guidelines before the test.The participants’ strength endrance were evaluated with the use ofthe 3-MBT. The results were processed statistically by calculatingthird-order partial correlation coefficients. Results. Raw scorecorrelation coefficients were statistically significant (p-values: 0.05-0.01), excluding body height which was not bound by significantcorrelations with the number of cycles completed by women ineach minute of the 3-MBT and the number of cycles completedby men in the first minute of the 3-MBT. However, the third-orderpartial correlation analysis demonstrated that PA level was theonly independent variable that was significantly correlated withthe results scored in the entire 3-MBT and in successive minutes ofthe test. In both sexes, the lowest values were observed in the firstminute, and they were considerably higher in the second minute ofthe test. Conclusions. In the group of the analyzed variables, only PAlevels significantly influence the strength endurance of moderatelyphysically active young women and men during the 3-MBT.
Keywords: strength endurance; extreme efforts; university students; 3-Minute Burpee Test